Caring and Curing Historical Perspectives on Women and Healing in Canada - Dodd, Dianne (Social Sciences, 1994)
This collection of essays takes the reader from the early 19th century struggle between female midwives and male physicians right up to the late 20th century emergence of professionally trained women physicians vying for a place in the medical hierarchy. The bitter conflict for control of birthing and other aspects of domestic health care between female lay healers, particularly midwives, and the emerging male-dominated medical profession is examined from new perspectives.